'We have education, I can say that': worldview and access to education for adult refugees. (7th September 2016) - Perry, Kristen H.; Mallozzi, Christine A.
Abstract : We present a discourse analysis of narratives from two adult Congolese refugees, focused on the influence of worldview (including cultural mindset, personal world, and perspective ) on thinking about accessing higher education. We examined narrative structure (Gee 2011), subject statements, and Underhill's (2009) three elements of worldview in the narratives. Both participants held a cultural mindset that highly valued education, but their personal worlds and perspectives differed, perhaps explaining their different decisions about accessing higher education. Findings suggest implications for supporting adult refugee education, particularly their aspirations for accessing higher education.